From Risk Profiling to Enterprise Resilience: Interdependencies in Management - Sylwia Bąk; Piotr Jedynak (Routledge, 2024)
From Risk Profiling to Enterprise Resilience introduces readers to a new approach to risk profiling theory and methodology, as well as relationships between an enterprise's risk profile and its resilience to crises. Given the need to reflect on changes in approaches to risk and risk management in the aftermath of the COVID-19 pandemic, the book attempts to characterize the interdependencies between risk profiling processes and the processes of shaping and improving enterprise resilience. After reading the book, the readers will firstly gain theoretical knowledge of risk management in non-crisis and crisis conditions, risk mitigation and risk profiling. Secondly, they will also acquire the practical skills of performing risk profiling, identifying risk mitigation actions, perceiving relationships between individual enterprises' risk profiles (and their changes), and the building and improving of their resilience. The inclusion of graphics, tables, diagrams, charts, instructions and recommendations will make the content is also easy to understand for a non-specialist audience. This book will be of great interest entrepreneurs, managers and risk management professionals, who can use the content included in the book in their management processes, as well as stakeholders of various enterprises, business and academic communities and students of all levels.
Keywords: 330; enterprise resilience; risk profiling; risk management; risk mitigation; COVID-19 pandemic